Freud for beginners - Osborne, Richard, 1952-; Mechan, Maurice (New York, NY : Writers and Readers Pub., 1993)
An introduction to Sigmund Freud's theories and arguments on self-perception, interpersonal relationships, and human behavior.
Includes bibliographical references (p. 171) and index.
Young Adult
Keywords: Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939.; Psychoanalysis; Psychoanalysts -- Austria -- Biography; Psychoanalysis; Psychoanalysts -- Biography